Reciprocal Salami-Slicing in East Asia - Sa, Harry (2016)
China’s land reclamation in the Spratly Islands has prompted critics to attack the Obama Administration for having been caught flat-footed yet again by cunning Chinese “salami-slicing” tactics. These critics fail to appreciate that the administration has actually been a more successful practitioner of those same tactics.